Undescribed and known phenolic acid derivatives with significant antioxidant activity from the Scorzonera parviflora Jacq. roots - Acıkara, Özlem Bahadır; Ataman, Ufuk; Zidorn, Christian; Cvacka, Josef; Kurtul, Ekin; Buděšínský, Milos; Bednarova, Lucie; Sarıaltın, Sezen Yılmaz (Fitoterapia, 2025)
The antioxidant activity of Scorzonera parviflora Jacq. roots were assessed by measuring their ability to scavenge ABTS and DPPH radicals. Bioactivity-guided fractionation was utilized to identify the compound(s) responsible for this activity. The most active phase, ethyl acetate, was isolated using column chromatography. The resulting fractions were then purified using preparative TLC on reverse phase and semi-preparative HPLC. The structures of the pure compounds were elucidated by spectral analysis (MS and 1H, 13C, 2D-NMR). Three undescribed phenolic acid derivatives, namely parvifloric acid A (1), B (2), and C (3), and one new sesquiterpene lactone, parviflorin (4) together with seven known compounds were isolated and identified as scopolin (5), scopoletin (6), caffeic acid (7), protocatechuic acid (8), 4,5-O-dicaffeoylquinic acid (9) 3,5-O-dicaffeoylquinic acid (10), and 3,5-O-dicaffeoylquinic acid methyl ester (11). Finally, the pure compounds obtained were tested to evaluate their antioxidant capacities, using ABTS and DPPH radical scavenging potencies. The highest activity was observed with 3,5-O-dicaffeoylquinic acid (10), followed by its methyl ester.
Keywords: Asteraceae; Molecular Structure; Sesquiterpene lactone; Phenolic acids; molekulární struktura; fytonutrienty; Antioxidants; Phytochemicals; Antioxidant activity; Scorzonera parviflora; Plant Roots; hydroxybenzoáty; kořeny rostlin; Hydroxybenzoates; Sesquiterpenes; antioxidancia; seskviterpeny; Scorzonera